Использование метода классификационных деревьев для анализа связи структура аффинитет лигандов 5-НТ1A рецепторов - Полищук, П.Г.; Кузьмин, В.Е.; Артеменко, А.Г.; Макан, С.Ю.; Андронати, С.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The analysis of the structure-affinity relationship for 347 ligands of 5-HT1A receptors is made by the method of classification trees. The procedure which allows one to estimate the relative influence of structural fragments on the investigated activity in the context of this algorithm is developed. Structural fragments and their influence on the affinity to 5-HT1A receptors are determined.